Evaluation of Online Log Variables that Estimate Learners’ Time Management in a Korean Online Learning Context - Jo, Il-Hyun; Park, Yeonjeong; Yoon, Meehyun; Sung, Hanall (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The purpose of this study was to identify the relationship between the psychological variables and online behavioral patterns of students, collected through a Learning Management System (LMS). Test was attempted of a structural equation model representing the relationships among Time and Study Environment Management (TSEM), one of the sub-constructs of MSLQ, influencing a set of time-related online log variables: login frequency, login regularity, and total login time. Data were collected from 188 college students in a Korean university. Employing structural equation modeling, a hypothesized model was tested for measuring the model fit. The results presented a criterion validity of online log variables to estimate their time management. The structural model including TSEM, online variable, and final score with a moderate fit indicated that learners’ time related online behavior mediates their psychological functions and their learning outcome. Based on the results, the final discussion includes the recommendations for further study and the meaningfulness in regard to the expantion of Learning Analtyics for Performance and Action (LAPA) model.